Fire and legume germination in a tropical savanna: ecological and historical factors - Daibes, L Felipe [UNESP]; Pausas, Juli G.; Bonani, Nathalia [UNESP]; Nunes, Jessika [UNESP]; Silveira, Fernando A O; Fidelis, Alessandra [UNESP] (Oxford University Press (OUP), 2019)
BACKGROUND AND AIMS: In many flammable ecosystems, physically dormant seeds show dormancy-break patterns tied to fire, but the link between heat shock and germination in the tropical savannas of Africa and South America remains controversial. Seed heat tolerance is important, preventing seed mortality during fire passage, and is usually predicted by seed traits. This study investigated the role of fire frequency (ecological effects) and seed traits through phylogenetic comparison (historical effects), in determining post-fire germination and seed mortality in legume species of the Cerrado, a tropical savanna-forest mosaic. METHODS: Seeds of 46 legume species were collected from three vegetation types (grassy savannas, woody savannas and forests) with different fire frequencies. Heat shock experiments (100 °C for 1 min; 100 °C for 3 min; 200 °C for 1 min) were then performed, followed by germination and seed viability tests. Principal component analysis, generalized linear mixed models and phylogenetic comparisons were used in data analyses. KEY RESULTS: Heat shocks had little effect on germination, but seed mortality was variable across treatments and species. Seed mortality was lowest under the 100 °C 1 min treatment, and significantly higher under 100 °C 3 min and 200 °C 1 min; larger seed mass decreased seed mortality, especially at 200 °C. Tree species in Detarioideae had the largest seeds and were unaffected by heat. Small-seeded species (mostly shrubs from grassy savannas) were relatively sensitive to the hottest treatment. Nevertheless, the presence of physical dormancy helped to avoid seed mortality in small-seeded species under the hottest treatment. CONCLUSIONS: Physical dormancy-break is not tied to fire in the Cerrado mosaic. Heat tolerance appears in both forest and savanna species and is predicted by seed traits (seed mass and physical dormancy), which might have helped forest lineages to colonize the savannas. The results show seed fire responses are better explained by historical than ecological factors in the Cerrado, contrasting with different fire-prone ecosystems throughout the world.
Keywords: Cerrado; Fabaceae (Leguminosae); fire ecology; heat shock; physical dormancy; seed traits; tropical savanna